Bosques de aprendizajes - Martín, Rocío Belén (2023)
Autores/as Bárbara Noelia Bárcena Esquivel - Juan Manuel Brito - Agustín Davies – Santiago de la Torre Manca– Erika Díaz – Danilo Donolo - Pablo Emanuel – Diego Fabián – Alejandra Frausto Aceves - Gimena Fussero – Leticia Garcia Romano - Sebastián Gabriel Herrera – Giuliana Lingua - Rocío Belén Martín – Rebeca Martinenco – Marina Masullo – Giuliana Morbidoni Davicino - Maricel Occelli - A. Carolina Otero - Nahuel E. Palombo –María Belén Pérez – Javier Poblete - Brisa Rodríguez Paz - Sara Tolbert - Betzabe Torres Olave - Madelaine Vieyra – Santiago Villane